Entry into Insular Domains: A Longitudinal Study of Knowledge Structuration and Innovation in Biotechnology Firms - GEORGE, Gerard (Institutional Knowledge at Singapore Management University, 2008)
We focus on the firm's decision to enter insular technology domains and its effect on the impact that its subsequent innovation has on the field. Insular domains are technical domains that rely heavily on prior innovations within the same domain for subsequent innovations. We show that the returns to entering insular domains vary with the firm's depth and breadth of knowledge. By analysing data from 128 biotechnology firms over a 20-year period, we find that the relationship between depth of technological capabilities and technology impact is nuanced: depth is necessary but not sufficient for high impact innovation. Firms whose knowledge is spread over disparate domains have negative returns from entering insular domains. The implications of these findings for theories of innovation and the discovery of entrepreneurial opportunities are discussed.